Application of telerehabilitation in home care for older adult patients with postoperative hip fractures: A scoping review - Chanli Yang; Yingping Fu; Di Du; Xiaojuan Li; Qin Zhou; Yuan Yang; Tianxian Luo (PLoS ONE, 2026)
Background As the older adults population grows, the incidence of hip fractures continues to rise, presenting a major challenge to healthcare systems. Traditional postoperative rehabilitation often struggles with continuity and accessibility, particularly for patients in remote areas. Telerehabilitation, which leverages digital technologies for remote care, is emerging as a potential solution to overcome these limitations and provide more efficient, accessible rehabilitation for older adult patients recovering from hip fractures. Objective To conduct a scoping review of studies on the application of telerehabilitation in home care for older adults postoperative hip fractures, aiming to evaluate its effectiveness, methods, and potential for standardization in clinical practice. Methods Based on scoping review guidelines, a systematic search was conducted on CNKI, Wanfang Database, CQVIP, CBM, PubMed, Web of Science, Cochrane Library, CINAHL, and Embase, up to August 31, 2025..The included literature was summarized and analyzed. Results A total of 18 studies were included. Among these, mobile applications, WeChat platforms, and video interaction systems were the primary methods for home-based care of elderly patients after hip fracture surgery, all utilizing telerehabilitation delivered through video, text, and image-based interventions. A meta-analysis of key outcome measures revealed significant improvements in the telerehabilitation group compared to the control group across several domains: hip function (HHS, P < 0.001), walking ability (6MWT, P < 0.0001), and quality of life (SF-36, P < 0.001). Furthermore, advantages were noted in pain relief (NPRS, P < 0.05) and a reduction in depressive symptoms (HADS-D, P = 0.003). Notably, multiple studies consistently reported significantly higher exercise adherence in the telerehabilitation group compared to the control group (P < 0.05). Conclusion Telerehabilitation effectively enhances functional recovery and adherence in older adults after hip fracture surgery. Its success depends on matching interventions to patients’ digital literacy. Future implementation requires standardized protocols and outcome measures to be integrated into professional follow-up care, thereby overcoming existing barriers and maximizing scalability. Trial registration OSF Registration DOI: https://doi.org/10.17605/OSF.IO/QYUJM